Case reportEffectiveness of omalizumab in a patient with a life-threatening episode of bronchospasm and larynx angioedema after exposure to house dust - Kupryś-Lipińska, Izabela; Korczyńska, Paulina; Tworek, Damian; Kuna, Piotr (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Omalizumab is a monoclonal antibody against IgE, nowadays approved for the treatment of persistent severe (EU) or moderate-to severe (USA) IgE-mediated asthma but there is also some evidence (case reports and four published clinical trials) on the effectiveness of this medication in urticaria and angioedema. The case of a 42-year-old woman suffering from severe allergic asthma and severe chronic urticaria with concomitant angioedema is presented in the article. She had a life-threatening episode of bronchospasm and larynx edema after exposure to house dust recorded in her medical history. The patient did not respond to standard therapy. The improvement in asthma control and remission of chronic urticaria and angioedema was achieved after introducing the therapy with omalizumab.